PENGARUH PENDIDIKAN KESEHATAN TERHADAP PERILAKU CUCI TANGAN PAKAI SABUN DENGAN AIR MENGALIR ANAK SD DI SEKOLAH DASAR NEGERI 157019 PINANGSORI 12 KABUPATEN TAPANULI TENGAH TAHUN 2018 - Rumiris Simatupang; Meiyati Simatupang (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2019)
Abstract Clean and Healthy Behavior (PHBS) is a set of behaviors that are practiced on the basis of awareness as a learning outcome, which makes a person, family, group and community able to help themselves (independent) in the health sector and play an active role in realizing public health. Clean and healthy life behavior is the second biggest factor after environmental factors that have an impact on the health of individuals, groups or communities. The purpose of this study was to determine the effect of health education on the behavior of washing hands with soap with running water in elementary school children in the 157019 Pinangsori Public Elementary School 12 Middle Tapanuli Regency 2018. This study used a Quasi Experimental research method using one group pretest-posttest design. The sample in this study was elementary school students grade IV at SDN Pinang Sori 12. Sampling used a total sampling technique with a number of respondents as many as 56 people. The results of the study t value of the variable knowledge was -9,151 with a p value of 0,000 <0.05 while the t value for the attitude variable is -15,394 with a p value of 0,000 <0.05 and the calculated value for the action variable is -12,699 p value of 0,000 <0.05 using the paired t-test static test then, it is concluded that there is an influence PHBS counseling about washing hands on knowledge and attitudes and actions about washing hands in elementary school class IV Pinang Sori 12. Keywords: Health Education, Knowledge, Attitudes, Actions